Cervical and Vulvar Intraepithelial Neoplasia after Treatment with Oral Isotretinoin for Severe Acne Vulgaris - M.N. Al Hallak; N. Zouain (Karger Publishers, 2009)
Oral isotretinoin is the drug of choice for severe acne vulgaris, but its use is still controversial in preventing, treating or stopping the progression of the cervical intraepithelial neoplasia [6-8]. It induces cell differentiation, inhibits cell proliferation, stimulates host immune reaction, inhibits the oncogene expression, augments cell-mediated cytotoxicity, and induces apoptosis [5]. The isotretinoin has many side effects including teratogenicity. There is no previous report of developing cervical intraepithelial neoplasia (CIN) or vulvar intraepithelial neoplasia (VIN) after introducing oral isotretinoin to a patient. We are reporting a 37-year-old female with no risk factors for cervical cancer who had developed CIN-I and VIN-I during a 6-month treatment period of oral isotretinoin for her severe acne vulgaris. Interestingly, the patient had complete spontaneous pathologic-proven remission after stopping the isotretinoin. Further case reports are warranted to support this incidence.